Nonlinearities investigation and experimental validation insights into mechanical model of yoke-type inerter for enhanced vibration suppression - Zhang, Ruifu; Tao, Qian; Zhang, Li; Hao, Linfei; Xue, Songtao (Scientific reports, 2025)
Yoke-type inerters demonstrate adaptive apparent mass properties and dynamic negative stiffness characteristics; however, prior research has yet to establish an engineering-applicable mechanical constitutive model, thereby constraining their implementation in structural vibration control applications. This study proposes a multi-body dynamics-derived constitutive model that considers backlash-induced collision effects in yoke-type inerters, accompanied by experimental validation. Building upon established theoretical frameworks, a constitutive model is first formulated to incorporate inertial forces, Coulomb friction, and backlash nonlinearities. Subsequently, experiments are conducted on a prototype yoke-type inerter. To rigorously characterize the device’s nonlinear behaviors arising from backlash and collision, a multi-body dynamics simulation is implemented, which facilitates the development of an enhanced constitutive model integrating collision. The enhanced model is then employed to quantitatively assess the influence of the backlash and collision on vibration isolator response. Experimental findings confirm the yoke-type inerter’s the adaptive apparent mass effect and dynamic negative stiffness characteristics, suggesting its potential as a viable mechanism for advanced vibration mitigation systems. Comparative analysis reveals that simulation results obtained through the proposed multi-body dynamics model demonstrate strong concordance with experimental trends, thereby verifying both model validity and predictive accuracy. Parametric studies further establish that backlash-induced collision effects exert influence on isolator dynamic responses. The developed modeling framework provides critical theoretical foundations for optimized design of yoke-type inerter-enhanced structures, advancing practical applications in high-performance vibration suppression engineering.